Luteolin mitigates oxidative stress and multi-organ impairment in a propionic acid-induced rodent model of autism - Khayyat, Arwa Ishaq Abdulmalik; Alabdali, Altaf N.; Alonazi, Mona; Alzahrani, Areej Ali; Al-Shehri, Eman; Ben Bacha, Abir (Frontiers in Nutrition, 2025)
Background/objectivesOxidative stress, organ impairments, and gastrointestinal abnormalities are the most common systemic dysfunctions that accompanied the neurodevelopmental condition, Autism Spectrum Disorder (ASD). Emerging evidence suggests that increased propionic acid (PPA) levels contribute to ASD pathophysiology through oxidative stress, neuroinflammation and disruption of the gut-liver-brain axis. Thanks to its strong anti-inflammatory and antioxidant potencies, luteolin, has shown to be promising in alleviating these effects. This study investigated the therapeutic and protective effects of luteolin in a PPA-induced rodent model of ASD by assessing oxidative stress, intestinal permeability, and liver and kidney dysfunction biomarkers.MethodsFifty young male albino rats were divided into five groups: control, PPA-treated, luteolin-treated, therapeutic (PPA followed by luteolin), and protective (luteolin followed by PPA). Oxidative stress markers (GSH, lipid peroxides, GST, SOD, and catalase), serum zonulin, liver enzymes (ALT, AST, ALP) and renal function markers (urea nitrogen, creatinine) were investigated. ROC analysis evaluated the diagnostic potential of these biomarkers, while Spearman correlation analysis explored interrelationships among parameters.ResultsPPA administration significantly reduced antioxidant defenses, including GSH, GST, SOD, and catalase, while increasing lipid peroxidation and inducing hepatic and renal dysfunction, as evidenced by elevated ALT, AST, ALP, urea nitrogen, and creatinine levels, along with increased zonulin levels. Luteolin intervention effectively reversed these alterations by restoring antioxidant capacity, lowering zonulin levels, and improving liver and kidney function. ROC analysis demonstrated high diagnostic accuracy (AUC = 1.000) for oxidative stress and organ dysfunction markers in the PPA-treated group, while luteolin treatment significantly enhanced biomarker sensitivity and specificity. Spearman correlation analysis revealed strong negative correlations between antioxidants and oxidative stress markers (p < 0.001) and positive correlations between zonulin and liver/kidney dysfunction indicators (p < 0.001), further confirming the systemic impact of PPA.ConclusionLuteolin effectively alleviated oxidative stress, restored antioxidant defenses, and enhanced liver, kidney, and intestinal barrier functions in a PPA-induced ASD model. These findings underscored its therapeutic potential as a natural intervention for ASD-related systemic dysfunctions. Further clinical studies are needed to evaluate its translational applicability in ASD management.